Long-term outcomes of very-low-birth-weight and low-birth-weight preterm newborns with neonatal seizures: A single-center perspective. (January 2022) - Schüssler, S.C.; Schmidt, M.; Deiters, L.; Candova, A.; Fahlbusch, F.B.; Trollmann, R.
Abstract: Objective: Newborn seizures are frequent in preterm newborns and indicate brain lesions in many cases. The objective of this observational study was to investigate the long-term outcome of very-low-birth-weight (VLBW) and low-birth-weight (LBW) preterm infants with neonatal seizures. Methods: We examined 54 preterm infants (40 VLBW and 14 LBW cases) born between 2008 and 2011 with clinical seizures during the neonatal period confirmed by interictal or ictal electroencephalography recordings in a retrospective single-center study. Neurodevelopmental follow-up included an expert neurological examination and cognitive testing (Kaufman Assessment Battery for Children) at a mean age of six years. Results: The (mean ± standard deviation) gestational ages of the VLBW and LBW infants were 27.2 ± 1.9 weeks and 33.4 ± 1.7 weeks, respectively, and the postnatal age at seizure onset was 13 ± 11 days in VLBW infants and 9 ± 8 days in LBW infants, with a wide range of one to 62 days. LBW infants more frequently developed non-motor seizures (50.0%) than VLBW infants did (25.0%), and higher-grade intracranial hemorrhage was the predominant etiology in the VLBW group (18.0%), while the etiology in the LBW group was more heterogeneous and included central nervous system malformations and genetic syndromes. At the mean age of 6.2 ± 2.0, years, 25/54 patients were assessed and 44.4% of the VLBW group and 71.4% of the LBW group showed intellectual impairment. Infantile cerebral palsy was present in 22% of VLBW and 42.9% of LBW infants, respectively. Significance: The present analysis of long-term neurodevelopmental outcomes of preterm neonates who experienced seizures shows that the risk for intellectual impairment is not limited only to VLBW infants but may significantly affect LBW infants as well. The etiological spectrum differs in relation to gestational age. Graphical abstract: Image 1 Highlights: Etiology of neonatal seizures is different in LBW and VLBW preterm infants. Postnatal age at seizure onset is later in the preterm infant compared to the full-term infant. Subtle seizures are common in LBW infants and carry a risk of cognitive impairment at school age.